Autologous Bone Marrow-Derived Mononuclear Cells Combined With β-TCP for Maxillary Bone Augmentation in Implantation Procedures. Issue 6 (November 2012) - Bulgin, Dmitry; Hodzic, Enes
Abstract : Abstract: Replacing missing bone or adding mass to existing bone is often essential to the success of a dental implant. A large variety of graft materials have been used for maxillary and mandibular atrophy. To date, there has been no graft material which can be regarded as completely satisfactory. Our experience with freshly isolated autologous bone marrow-derived mononuclear cells combined with β-tricalcium phosphate for augmentation of the extremely atrophied maxilla is presented. The techniques are based on stimulation of natural events continuously present in living bone, that is, the process of bone remodeling. The property of the mixture material for bone augmentation to place dental implant was discussed.